Evaluation of the International Community Service Program: The Influence of FOMO, Perception of Program Benefits on Student Motivation with the Moderating Variable of Financial Literacy - Syahfina, Rifki; Athar, Gadis Arniyati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the influence of FOMO and program benefits on students' motivation to participate in International Community Service Programs with financial literacy as a moderating variable. The research uses a quantitative approach with Moderated Regression Analysis (MRA). The research results show that financial literacy is the main factor influencing students' motivation to participate in the International Community Service Program. The FOMO variable does not have a significant effect on motivation, although financial literacy can change its influence in a positive direction. Initially, the program benefits had an impact on motivation, but it became insignificant when financial literacy was included in the model. The results of the moderation analysis show that financial literacy does not act as a moderating variable, but rather as a variable that directly influences students' motivation. These findings indicate that students' decisions to participate in the International Community Service Program are more influenced by considerations of their financial capabilities. Therefore, universities need to provide financial support such as scholarships, cost subsidies, and collaboration with foreign partners to increase student participation.